Inclusive learning patterns in islamic religious education materials at the elementary school of pondok pesantren modern uswatun hasanah lubuk linggau - Muhammad Iqbal Hidayatullah; Saiful Anwar; Ayu Era Wardhani (At Turots: Jurnal Pendidikan Islam, 2026)
This study aims to describe the inclusive learning patterns of Islamic Religious Education (PAI) at the Elementary School of Pondok Pesantren Modern Uswatun Hasanah Lubuklinggau, covering the planning, implementation, and evaluation of learning for students with special needs. Employing a descriptive qualitative approach, data were collected through observations, in-depth interviews, and documentation, and analyzed using the Miles and Huberman interactive model, with data validity ensured through source triangulation. The findings indicate that learning planning involves assessing learner needs, developing adaptive teaching modules based on the Merdeka Curriculum, and formulating individualized objectives; implementation adopts a holistic approach rooted in Islamic values with flexible methods and strong collaboration between homeroom teachers and assistant teachers; and evaluation prioritizes process-oriented assessment through daily observation, developmental journals, alternative assessments, and parental involvement. Overall, the inclusive learning model demonstrates an effective integration of pesantren culture, Islamic values, and inclusive pedagogy, offering a valuable reference for other Islamic educational institutions seeking to strengthen inclusive practices.